Análise cinemática da marcha de amputados transtibiais: comparação dos encaixes KBM e a vácuo - Ferreira, Alana Elisabeth Kuntze (2014)
Introduction: Transtibial amputation is one of the lower limb amputations more often performed. Objective: The aim of this study was to compare, using 3D gait analysis, gait deviations of patients with transtibial amputation, previously trained, using KBM and vacum prosthetic fittings. Methodology: Transtibial amputees that used Kondylen Bettung Münster (KBM) and vacuum prosthetic fitting waived by the Sistema Único de Saúde (SUS) were evaluated. The final sample consisted of 12 participants in the "KBM" group and 5 in the "vacuum" group. They all underwent a physical examination, which consisted of goniometry, muscle strength testing and anthropometric data. They also performed three-dimensional (3D) gait analysis. For this, they were vested with reflexive markers on anatomical and prosthetic corresponding landmarkers according to the Helen Hayes and walked across a 10-m walk-way at their self-selected speed. The capture system consisted of 6 cameras Hawk and the Cortex software version 1.1.4.368 for capturing and editing the trials, both from Motion Analysis Corporation. The Gait Profile Scores (GPS), Gait Variable Score (GVS) and temporal-spatial parameters performed the comparison between the two groups. In addition, we tested the correlation between GPS and GVS and between GPS and temporal-spatial parameters. Results: The two groups had significantly lower gait speed, significantly longer period of support and shorter time of single support than normal. In both groups, GPS and GVS values were higher than normal, but the "KBM" showed greater deviations than the "vacuum". The largest deviations from the KBM group was in the GVS hips flexion / extension, knees flexion / extension and ankle dorsi / plantarflexion MIP and can thus characterize this as the deviation pattern of the Movement Analysis Profile (MAP) for this group. The "vacuum" group had major deviations of the GVS ankles dorsi / platarflexion, knee flexion / extension MIP and pelvic rotation, the deviation pattern of MAP in this group. There were, therefore, different deviation patterns I the two groups. Both groups showed deviations in MICL, which represent the compensation made by this limb to enable a more functional gait with prosthesis. Participants who used vacuum prosthetic fitting showed more a symmetrical gait than participants that used KBM prosthetic fitting. The group that used vacuum prosthetic fitting had lower values of GPS and some GVS than "KBM" group; these include hips flexion / extension, MIP knee flexion / extension and MICL knee flexion / extension, which was the only statistically significant difference between the groups. The same group had greater walking speed than the "KBM" group and, although this difference was not significant, it suggests more functionality of gait with vacuum prosthetic fitting. Conclusion: It can be concluded that individuals who used the vacuum prosthetic fitting showed more functional gait pattern and smaller deviations than those that used KBM prosthetic fitting, compared by GPS, GVS and temporal-spatial parameters.